Indicators of Financial Distress Condition in Nepalese Banking Industry - Lamichhane, Manisha; Tamang, Manju; Khadka, Nisha; Gautam, Nitisha (Nepalese Journal of Business, 2025)
The study examines the indicators of financial distress condition in Nepalese banking industry. Non-performing loan and Altman Z-score are selected as the dependent variables. The selected independent variables are debt ratio, return on assets, capital adequacy ratio, interest coverage ratio, retained earnings to total assets, and loan to deposit ratio. The study is based on secondary data of 10 commercial banks with 100 observations for the period from 2013/14 to 2022/23. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of indicators of financial distress condition in Nepalese banking industry. The major conclusion of this study is that debt ratio has a negative impact on Altman Z-score and non-performing loan. It indicates that higher the debt ratio, lower would be the Altman Z-score and non-performing loan. Similarly, return on assets has a positive impact on Altman Z-score. It indicates that increase in return on assets leads to increase in Altman Z-score. In contrast, return on assets has a negative impact on non-performing loan. It indicates that increase in return on assets leads to decrease in non-performing loan. However, capital adequacy ratio has a positive impact on Altman Z-score. It indicates that higher the capital adequacy ratio, higher would be the Altman Z-score. In contrast, capital adequacy ratio has a negative impact on non-performing loan. It indicates that increase in capital adequacy ratio leads to decrease in non-performing loan. In addition, interest coverage ratio has a positive impact on Altman Z-score. It indicates that higher the interest coverage ratio, higher would be the Altman Z-score. In contrast, interest coverage ratio has a negative impact on non-performing loan. It indicates that increase in interest coverage ratio leads to decrease in non-performing loan. Moreover, loan to deposit ratio has a positive impact on Altman Z-score and non-performing loan. It indicates that higher the loan to deposit ratio, higher would be the Altman Z-score and non-performing loan.